Establishment of an experimental model of normal dog bladder organoid using a three-dimensional culture method - Mohamed Elbadawy (Biomedicine & Pharmacotherapy, 2022)
Dog bladder cancer (BC) is mostly muscle-invasive (MI) with poor prognosis, and its pathogenesis is close to human MIBC. Three-dimensional (3D) organoid culture ensures novel knowledge on cancer diseases including BC. Recently, we have established dog BC organoids (BCO) using their urine samples. BCO recapitulated the epithelial structures, characteristics, and drug sensitivity of BC-diseased dogs. However, organoids from dog normal bladder epithelium are not established yet. Therefore, the present study aimed to establish dog normal bladder organoids (NBO) for further understanding the pathogenesis of dog BC and human MIBC. The established NBO underwent various analyzes including cell marker expressions, histopathological structures, cancer-related gene expression patterns, and drug sensitivity. NBO could be produced non-invasively with a continuous culturing and recapitulated the structures and characteristics of the dog's normal bladder mucosal tissues. Different drug sensitivities were observed in each NBO. The analysis of RNA sequencing revealed that several novel genes were changed in NBO compared with BCO. NBO showed a higher expression of p53 and E-cadherin, but a lower expression of MDM2 and Twist1 compared with BCO. These results suggest that NBO could be a promising experimental 3D model for studying the developmental mechanisms of dog BC and human MIBC.